Patient’s Perception about use of Personal Digital Assistants/ Smart Phones by Physiotherapists - Rabia Majeed, Syeda Sabahat Batool, Tamknat Ilyas, Wajiha Khan, Samer Zehra, Momina Najeeb, Irum Mushtaq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mobile phone is the need of present era in almost all fields of life. The demand of mobile phone has been increased thousand times because of emergence of smartphone. A smartphone works efficiently that it replaced computer systems and much more. Methodology: This study was a cross-sectional survey. It was completed in 4 months of duration. Data was collected from Public and private clinical setups having facility of outdoor physiotherapy services. Data was collected from physiotherapy patients. Both male and female physiotherapy patients aged between 15 to 70 were included in this study. Patients with cognitive impairments and not willing to participate or signing a consent were excluded from this study. Nonprobability Convenient sampling technique was used. The questionnaire has been adopted from previous literature. (11) Data was analyzed using Statistical Package for Social Sciences (SPSS 20.0). Data was analyzed in way that Numbers and percentages was calculated for demographics. Mean, standard deviation was calculated for total scores and continuous variables. Results: The result shows that 38.7% of the participants were male and 61.3% of the participants were females. The result shows education of the participants as 11.3% under metric, 10.7 % metric, 28.7% intermediate, 34% Bachelors, 12% Masters and 3.3% higher respectively. Moreover, the results of current study shows that 14.7% said no, 16% said don’t know and 69.3% said yes about knowledge of performance of your doctor on this device: Information look up. The result shows that 19.3% said no, 14% said don’t know and 66.7% said yes about knowledge of performance of your doctor on this device: Look up information about how to treat an illness. Conclusion: There found a moderate to high level of positive perception regarding use of personal digital assistants/ smart phones by physiotherapists. Furthermore, there found a direct correlation between knowledge and perception of smart devices i.e., higher knowledge, more positive the perception found.